The Struggle for Influence in the South China Sea: Regional Geopolitical Competition - Kunkunrat, Kunkunrat (Dalihan Na Tolu: Jurnal Hukum, Politik dan Komunikasi Indonesia, 2023)
The South China Sea, as one of the main trade routes and a maritime region rich in natural resources, has become the main stage for countries in the Asia Pacific region to compete for political, economic and military influence. This research discusses the phenomenon of power struggles that occur in the South China Sea, the main focus is on geopolitical competition in this strategic region. This research uses a qualitative approach with descriptive methods. The research results show that competition in the South China Sea involves a complexity of geopolitical, geoeconomic and national interest factors. This region, rich in natural resources, especially oil and gas, is a source of tension between coastal states and external actors. China, as the dominant power in the region, shows high interest in the Nine-Dash Line territorial claims, raising concerns from ASEAN countries and the United States. The complexity of national identities and competition for natural resources creates power imbalances and conflict in the South China Sea. Solutions to overcome these challenges require multilateral cooperation and diplomacy involving all relevant parties, with the aim of achieving peace, security and balance of interests in the region.